Cancer mortality by site and fluoridation of water supplies. Issue 4 (December 1982) - Chilvers, C
Abstract : Site-specific cancer mortality data for 20 United States cities have been abstracted from United States Government publications to explore further the hypothesis that fluoridation of water supplies causes cancer. Changes in mortality (standardised for age, sex, and ethnic group) between 1958-62 and 1968-72 in 10 fluoridated and 10 non-fluoridated United States cities have been examined. Of the seven sites (or groups of sites) examined, for only one is there a statistically significant difference between the fluoridated and non-fluoridated cities with respect to average change in mortality. This difference, for cancers of the genital organs, favours the fluoridated cities. These data do not provide evidence of a positive association between fluoridation of water supplies and cancer of any of the sites considered.